Soil Quality of Maize and Chili Plants Based on Soil pH in Gemuhblanten Village - Nafisah Irfani Setiasiwi; Fianti Fianti; Ian Yulianti (Physics Communication, 2025)
Soil pH is an indicator of soil quality that is important to note because it  affects the balance of nutrients in the soil. This is important, especially to maintain the fertility of agricultural land. The purpose of this study was to analyze soil quality based on the soil pH of maize and chili plants. The research sample was taken on the agricultural land of Gemuhblanten Village, Gemuh District, Kendal Regency ins October 2022. Sampling was carried out at six points on each of the maize and chili field. The initial pH data obtained was then averaged. It was obtained that the average soil pH of maize plants was 7.75 which was in the "slightly alkaline" criteria. The average soil pH of chili plants is 7.08 which is a "neutral" criterion The soil pH value for maize plants is slightly higher than the good soil pH for maize plants. Meanwhile, the pH of the soil in chili plants meets a good soil pH value for chili plants.